Synergy and Accountability of Financial Supervision in Governance - Pranomo, Sigit; Istislam, Istislam; Hadiyantina, Shinta (IJBLE Scientific Publications Community Inc., 2025)
This research aims to analyze the implications of supervision that is not based on synergy and accountability and how the regulatory criteria are in accordance with the legislation. This research uses normative juridical research method with statutory approach and conceptual approach. The implications of supervision that is not synergistic and accountable can have conssequences in the form of the risk of corruption and budget abuse, inefficiency in managing state finances, and lack of transparency to the public. 2. The implications of non-synergistic and accountability-based oversight suggest that inefficient oversight increases the risk of corruption, budgetary misappropriation, and inefficiency in the management of the state budget. Furthermore, distorted transparency in the presentation of audit results reduces public confidence in the government's financial oversight system. Follow-up on irregularities is also slow due to differences in audit results and the absence of synergy between oversight institutions.